Effects of temperature on the carbonation of flue gas desulphurization gypsum using a CO2/N2 gas mixture - Lee, Myung Gyu (Environmental technology, 2015)
The carbonation of flue gas desulphurization (FGD) gypsum using a CO2/N2 gas mixture was investigated to study the feasibility of using the flue gas directly in the gypsum carbonation. The effect of the reaction temperature on the carbonation reaction and the carbonation conversion efficiency of the samples were considered. In this study, the carbonation conversion efficiency was calculated using a new method for decreasing the error range from a sample containing unreacted gypsum. The carbonation reaction at 40°C was nearly twice as fast as the reaction at room temperature. In addition, the carbonation conversion efficiency at 40°C (96%) was nearly the same as that at room temperature. However, the efficiency decreased significantly with temperature, especially above 60°C. It can, therefore, be concluded that the direct use of flue gas in gypsum carbonation is most feasible at 40°C. The temperature of carbonation strongly affected the CaCO3 polymorphs and the morphological characteristics. Calcite with various shapes was the dominant (40-90%) phase at all temperatures. At temperatures below 40°C, spherical-shaped vaterite was pronounced, while needle-flower-shaped aragonite was dominant at temperatures above 80°C